On the Grüss type inequalities within $p$-disks with applications - Alomari, Mohammad W. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.5We extend the classical Grüss inequality from Euclidean disks in $\mathbb{R}^2$ to generalized $p$-disks and present rigorous formulations for functions satisfying Hölder-type conditions. Several new Grüss-type inequalities are established and applied to establish bounds for the covariance of random variables defined either by probability density functions or by joint distributions.